Comparative immunohistochemical study of deep infiltrating endometriosis, lymph node endometriosis and atypical ovarian endometriosis including description of a perineural invasion - Lenz, Jiri; Chvatal, Radek; Fiala, Ludek; Konecna, Petra; Lenz, David (Biomedical papers, 2021)
Aim. Endometriosis is an inflammatory condition that shares a number of similarities with malignant diseases, such as an abnormal morphology, migration along the nerve bundles and metastatic spread to lymph nodes and distant organs. Endometriotic lesions are associated with oestrogen and progesterone imbalance which seems to play a key role in the pathogenesis of endometriosis. The aim of this study was to compare the status of both oestrogen and progesterone receptors in tissue of deep infiltrating endometriosis, lymph node endometriosis and atypical ovarian endometriosis using immunohistochemical methods, as well as to investigate the relationship between endometriosis and protein p53. Methods. A total of 40 cases with deep infiltrating endometriosis were included in our study. Based on histopathological analysis of resected specimens, the cases were divided into 2 groups: group 1 - lymph node endometriosis (cases with lymph node involvement; n=12) and group 2 - deep infiltrating endometriosis (cases without lymph node involvement; n=28). As a control group, eutopic endometrium of adenomyosis- and endometriosis-free women were used (n=16). Five cases of atypical ovarian endometriosis as well as descriptions of the nerve involvement in endometriosis were also included. Immunohistochemical staining with a total of 4 markers was performed - oestrogen and progesterone receptors (ER, PR), p53 and Ki-67 (proliferation index). Results. The immunophenotype of the cases in groups 1 and 2 and in the control group was virtually identical in the proliferative phase - strong nuclear ER and PR expression in more than 90% of endometrial glandular and stromal cells. In the early and mid secretory phase, ER expression only slightly decreased (80%) in endometrial glandular cells in group 2 and the control group, whereas in the late secretory phase, significant decrease of ER expression only in the control group was observed (15-50%; P<0.001). In group 2 and the control group, significant decrease of PR expression only in endometrial glandular cells was observed in the mid and late secretory phase (less than 15%; P<0.001). Differences in receptor content were found only in isolated cases in group 2. In group 1, no secretory changes were found. In all three groups, sporadic and weak nuclear p53 expression in less than 3% in both endometrial glandular and stromal cells was detected (regardless of the phase of the menstrual cycle). In atypical ovarian endometriosis, higher and strong p53 expression (on average 26%) and decrease in ER (on average 56%) and PR (less than 1%) expression was observed; compared to the control group and groups 1 and 2, the differences for all 3 markers were highly significant (P<0.001). In all groups, the proliferation index (Ki-67) reached the highest values in the proliferation phase and decreased during the cycle. However, in endometriotic tissue, it was widely variable in the individual phases of the cycle. Perineural spread of endometriosis with significant neural hypertrophy, hyperplasia and involvement of the ganglia of the autonomic nervous system was detected in 5 cases (12.5%). Conlusion. From a histological and immunohistochemical point of view, deep infiltrating endometriosis and lymph node endometriosis appear to represent the same entity. For the first time, a simple immunohistochemical panel with antibodies against ER, PR and p53 useful in diagnosing atypical endometriosis has been described. The marked endometriosis-associated neural changes (endometriotic neuropathy) could be one of the causes of impaired function of the affected organs after debulking surgery with macroscopic negative resection margins as well as pain symptomatology in macroscopic inapparent endometriotic lesions.
Keywords: deep infiltrating endometriosis; lymph node endometriosis; atypical endometriosis; immunohistochemistry; p53; perineural invasion